2010
DOI: 10.1007/s00535-010-0296-3
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of apelin receptor (APJ/AGTRL1) on hepatic stellate cells and sinusoidal angiogenesis in human cirrhotic liver

Abstract: Enhanced expression of APJ on HSCs in cirrhosis indicates markedly increased vascular remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 25 publications
4
37
0
Order By: Relevance
“…In addition, apelin contributes to platelet-derived growth factor-induced proliferation of HSC's in vitro [12], all of which are known to contribute largely to fibrosis progression and extracellular matrix deposition [30, 31]. In this setting, we also found apelin serum level to be significantly elevated in patients with fibrosis.…”
Section: Discussionsupporting
confidence: 57%
“…In addition, apelin contributes to platelet-derived growth factor-induced proliferation of HSC's in vitro [12], all of which are known to contribute largely to fibrosis progression and extracellular matrix deposition [30, 31]. In this setting, we also found apelin serum level to be significantly elevated in patients with fibrosis.…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies have demonstrated that apelin/APJ axis is one of the important signalling pathways involved in the pathological fibrotic processes, such as liver cirrhosis. Apelin and its receptor APJ are expressed at high levels in hepatic stellate cells (HSC) of human cirrhotic liver 10,18 . Pro‐fibrotic factors, such as angiotensin II and endothelin‐1, increase the expression of apelin in human LX‐2 HSC line, 10 whereas hypoxia and lipopolysaccaride stimulate the expression of APJ in those cells 19 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that APJ was expressed in Kupffer cells, and it inhibited liver regeneration after partial hepatectomy in mice (Yoshiya et al, 2015). In addition, the apelin/APJ was expressed in human hepatic stellate cells (HSCs), and promoted liver fibrosis or cirrhosis progression (Melgar-Lesmes et al, 2010; Yokomori et al, 2011). …”
Section: Distribution and Expression Of Apelin In Livermentioning
confidence: 99%
“…Melgar-Lesmes et al (2011) reported that apelin expression in HSCs was enhanced under hypoxic or proinflammatory conditions, and apelin could increase the synthesis of platelet-derived growth factor β receptor (PDGF-β) and collagen-I in LX-2 cells. Yokomori et al (2011) reported that, in cultured HSCs, APJ expression was sharply increased by PDGF-β. The function of apelin/APJ in liver fibrosis still needs to be investigated.…”
Section: Function Of the Apelin/apj In Physiology And Pathophysiologymentioning
confidence: 99%